Gene regulation associated with sexual development and female fertility in different isolates of Trichoderma reesei - Christoph Dattenböck; Doris Tisch; Andre Schuster; Alberto Alonso Monroy; Wolfgang Hinterdobler; Monika Schmoll (Fungal Biology and Biotechnology, 2018)
Abstract Background Trichoderma reesei is one of the most frequently used filamentous fungi in industry for production of homologous and heterologous proteins. The ability to use sexual crossing in this fungus was discovered several years ago and opens up new perspectives for industrial strain improvement and investigation of gene regulation. Results Here we investigated the female sterile strain QM6a in comparison to the fertile isolate CBS999.97 and backcrossed derivatives of QM6a, which have regained fertility (FF1 and FF2 strains) in both mating types under conditions of sexual development. We found considerable differences in gene regulation between strains with the CBS999.97 genetic background and the QM6a background. Regulation patterns of QM6a largely clustered with the backcrossed FF1 and FF2 strains. Differential regulation between QM6a and FF1/FF2 as well as clustering of QM6a patterns with those of CBS999.97 strains was also observed. Consistent mating type dependent regulation was limited to mating type genes and those involved in pheromone response, but included also nta1 encoding a putative N-terminal amidase previously not associated with development. Comparison of female sterile QM6a with female fertile strains showed differential expression in genes encoding several transcription factors, metabolic genes and genes involved in secondary metabolism. Conclusions Evaluation of the functions of genes specifically regulated under conditions of sexual development and of genes with highest levels of transcripts under these conditions indicated a relevance of secondary metabolism for sexual development in T. reesei. Among others, the biosynthetic genes of the recently characterized SOR cluster are in this gene group. However, these genes are not essential for sexual development, but rather have a function in protection and defence against competitors during reproduction.